Buckling analysis of carbon nanotube reinforced FG shells using an efficient solid-shell element based on a modified FSDT. (November 2019) - Hajlaoui, A.; Chebbi, E.; Dammak, F.
Abstract: This study investigates buckling behaviors of functionally graded carbon nanotube-reinforced composites (FG-CNTRC) shells using a modified first-order enhanced solid-shell element formulation. On that account, a parabolic shear strain distribution through the shell thickness in the compatible strain part is proposed. In fact, the shear correction factors are no longer needed. Five kinds of single-walled carbon nanotubes (SWCNTs) distribution through the thickness of layers are considered, namely, uniform (UD) and functionally graded (FG) symmetric and asymmetric. The buckling behavior of FG-CNTRC plate under uniaxial compressive pressure and FG-CNTRC cylindrical shell under external pressure and axial compression are considered. Comparisons of our numerical results with those reported by other investigators are presented in order to compare different formulations and to illustrate the performance of the developed solid-shell element. The result of the buckling behavior of CNTRC structure makes the present formulation appropriate for a wide range of structure plates and shells. Then, the effects of some geometrical and material parameters on the critical buckling load of shell structures are investigated. Highlights: Buckling analysis of carbon nanotube-reinforced FG shells is studied. Modified first-order enhanced solid-shell element is developed. Parabolic shear strain distribution through the shell thickness is imposed. The shear correction factors are no longer needed.